Success and patient satisfaction of immediately loaded zirconia implants with fixed restorations one year after loading - Rico Rutkowski; Ralf Smeets; Leon Neuhöffer; Carolin Stolzer; Kilian Strick; Martin Gosau; Susanne Sehner; Karl Ulrich Volz; Anders Henningsen (BMC, 2022)
Abstract Background There is limited evidence for the use of zirconium dioxide implants in immediate implant placement as well as for related immediate loading protocols. The aim of this retrospective study was to investigate the survival rate, success and patient satisfaction of immediately placed zirconia implants compared to delayed placed implants. Methods The study included 58 partially edentulous patients who were treated between 2013 and 2015 with immediate and delayed transgingival healing zirconium dioxide implants (SDS, Kreuzlingen/ Switzerland). In addition to survival and success rate, marginal bone loss was assessed using radiographs and soft tissue was evaluated using Pink Esthetic Score. Oral health-related quality of life was investigated prospectively using a modified OHIP questionnaire. Results The cumulative survival rate of all implants included was 92% with 88% classified as full success. No significant difference was found between the bone levels of immediately and delayed placed and immediately and delayed loaded implants. The mean Pink Esthetic Score after final prosthetic rehabilitation was 12.2/14 points indicating excellent esthetic clinical results. Analysis of the OHIP questionnaire showed a mean value of 0.54/100 points reflecting a high patient satisfaction. Conclusions Immediate and delayed placed as well as loaded zirconium dioxide implants showed excellent results regarding implant success and survival in this study. Zirconium dioxide implants may ensure excellent esthetic results and high patient satisfaction.